'Re-existence' of women Cambodian religious leaders: decolonial possibilities using insights from feminist relational theory and postsecular feminism. Issue 1 (2nd January 2022) - Schubert, Lara K.
ABSTRACT: Feminist relational theory can provide a theoretical framework for understanding and affirming the agency of women Cambodian religious leaders; an agency that can be overlooked if one assumes it comes from an individual whose core essence can be found apart from her relationships. In this paper, I draw on ethnographic fieldwork to spotlight the lives and values of two Cambodian women. These women are recognized as acting subjects in their communities due to their multiple relationships on interpersonal, institutional, and structural levels. Through analysis of participant observations and interviews with these women, I show the power of employing feminist relational theory's explanation of the agential subject while affirming the possibility of non-oppositional agency. The move to the latter is characteristic of postsecular feminist scholarship, which decouples resistance from agency. Using these two theoretical lenses to analyze Cambodian women's experience reveals how these women are flourishing apart from hegemonic structures and logics. This flourishing has been named 're-existence' in decolonial thought, and it might also be thought of as a postsecular analogue to a secular resistance.